1989
DOI: 10.1677/jme.0.003r005
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits Cyclic Amp Production in Cultured Ovine Pars Tuberalis Cells

Abstract: Primary cultures of ovine pars tuberalis (PT) cells of the pituitary were established to investigate the mode of action of melatonin. The heterogeneous population of cells was shown to bind the radioligand 2-[125I]-melatonin over 72 h in culture, although there was a progressive decline in specific binding with time. In cells cultured for 24 h, forskolin (1 μmol/l) was found to stimulate a 12-fold increase in cyclic AMP accumulation. This response could be inhibited by melatonin in a dose-dependent manner, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 0 publications
5
91
1
2
Order By: Relevance
“…The MEL receptors are coupled to G proteins and their activation often leads to the inhibition of the adenylyl cyclase, resulting in a decrease in the cAMP level of the cells [2,7,10]. Recently it has been reported that MEL is also able to influence the phosphoinositide breakdown in chicken brain slices [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MEL receptors are coupled to G proteins and their activation often leads to the inhibition of the adenylyl cyclase, resulting in a decrease in the cAMP level of the cells [2,7,10]. Recently it has been reported that MEL is also able to influence the phosphoinositide breakdown in chicken brain slices [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in the cells of the pars tuberalis MEL-sensitive receptors are functionally coupled to a G protein, which causes a decrease in the cyclic AMP level [2,7,10]. To test whether the expressed MEL-sensitive receptors are additionally able to influence the cyclic AMP level in oocytes, the effects of MEL on the action of forskolin, an unspecific activator of the adenylyl cyclase, was tested.…”
Section: Effects Of Mel On the Cyclic Amp Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Their activation induces a decrease in forskolin-induced cAMP accumulation (Carlson et al, 1989;Morgan et al, 1989). This effect is generally mediated by a pertussis toxinsensitive G-protein (G i /G o ; Reppert et al, 1994).…”
Section: Sites and Mechanisms Of Action Of Melatoninmentioning
confidence: 99%
“…These developments have added new impctus to attcmpts to understand the cellular and neural mechanisms of action of melatonin. In tissue explants of rat pituitary or hamster median eminence/pars tuberalis and in primary cells cultures of ovine Pars tuberalis, it has been demonstrated that melatonin is able to inhibit adenylate cyclase activity by acting through a receptor coupled to one or more inhibitory C-proteins (17)(18)(19)(20)(21)(22). In ovine pars tuberalis, melatonin does not acutely affect basal or stimulated levels of intracellular free calcium nor the turnover of inositol phosphates (23,24).…”
mentioning
confidence: 99%